2018
DOI: 10.1002/pmic.201700479
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Proteomic Analysis of Biological Processes and Responses of the BacteriumDesulfovibrio desulfuricansND132 upon Deletion of Its Mercury Methylation Genes

Abstract: Recent studies of microbial mercury (Hg) methylation revealed a key gene pair, hgcAB, which is essential for methylmercury (MeHg) production in the environment. However, many aspects of the mechanism and biological processes underlying Hg methylation, as well as any additional physiological functions of the hgcAB genes, remain unknown. Here, quantitative proteomics are used to identify changes in potential functional processes related to hgcAB gene deletion in the Hg-methylating bacterium Desulfovibrio desulfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 52 publications
(107 reference statements)
1
28
0
Order By: Relevance
“…We speculate that the fraction of HgcA is equivalent to approximately 0.0004% of the total protein concentration in cell lysates (see supplemental material), which would correspond to approximately 1 in 220,000 proteins in the cell lysate. Such low abundance would explain difficulties in identifying HgcA protein fragments and low transcript levels in previously published studies (20,27,28). The calculated kinetic parameters resulting from this HgcA abundance estimate are k cat ϭ 3 ϫ 10 Ϫ3 s Ϫ1 , and k cat /K m ϭ 9 ϫ 10 5 M Ϫ1 · s Ϫ1 .…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…We speculate that the fraction of HgcA is equivalent to approximately 0.0004% of the total protein concentration in cell lysates (see supplemental material), which would correspond to approximately 1 in 220,000 proteins in the cell lysate. Such low abundance would explain difficulties in identifying HgcA protein fragments and low transcript levels in previously published studies (20,27,28). The calculated kinetic parameters resulting from this HgcA abundance estimate are k cat ϭ 3 ϫ 10 Ϫ3 s Ϫ1 , and k cat /K m ϭ 9 ϫ 10 5 M Ϫ1 · s Ϫ1 .…”
Section: Discussionmentioning
confidence: 92%
“…Reverse transcription-PCR (RT-PCR) data from ND132 (20) and proteomics studies in ND132 (27) and G. sulfurreducens PCA (28) indicated that the abundance of HgcA and HgcB in Hg methylators is extremely low. Owing to the low abundance and resultant difficulties in determining accurate concentrations of HgcA and HgcB in the cell lysates, we used the obtained kinetic parameters to estimate turnover numbers (k cat ), catalytic efficiencies (k cat /K m ), and free energies of activation based on transition state theory (29,30) for a range of enzyme concentrations expressed as a fraction of total cellular protein concentration (Table 1, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We speculate that the fraction of HgcA is equivalent to approximately 0.0004% of the total protein concentration in cell lysates (see Supplementary Materials), which would correspond to approximately 1 in 220,000 proteins in the cell lysate. Such low abundance would explain difficulties in identifying HgcA protein fragments and low transcript levels in previously published studies (20,27,28). The calculated kinetic parameters resulting from this HgcA abundance estimate are k cat = 3·10 -3 s -1 , and kcat/KM = 9·10 5 M -1 · s -1 .…”
Section: Discussionmentioning
confidence: 89%
“…RT-PCR data from ND132 (20) and proteomics studies in ND132 (27) and G. sulfurreducens PCA (28) indicated that the abundance of HgcA and HgcB in Hg methylators is extremely low. Owing to the low abundance and resultant difficulties in determining accurate concentrations of HgcA and HgcB in the cell lysates, we used the obtained kinetic parameters to estimate turnover numbers (kcat), catalytic efficiencies (kcat/KM), and free energies of activation based on transition state theory (29,30) for a range of enzyme concentrations expressed as a fraction of total cellular protein concentration (Table 1, Fig.…”
Section: Enzyme Kinetics Of Hgcab-mediated Hg Methylationmentioning
confidence: 99%
“…In terms of coverage this is in with good keeping with other proteomic studies with metal trails in bacteria, including those of Desulfovibrio sp. (28, 29).…”
Section: Resultsmentioning
confidence: 99%